Comparative distribution of Lysyl Oxidase (G473A) and NQO1 (C609T) polymorphism among tea-garden workers (habitual chewers of betel quid) of Darjeeling district and Kolkata city of West Bengal - Jay Gopal Ray; Sanjit Mukherjee; Basudev Mahato; B H Sripathi Rao; Keya Chaudhuri (Wolters Kluwer Medknow Publications, 2013)
Context: Chewing of processed arecanut products with tobacco and betel quid has been attributed to many oral pathological conditions. These products are very popular among the youngsters of lower economic groups. Genetic predisposition has been now identified as a major risk factor for increasing the susceptibility toward the disease among these chewers. Aims: Our study mainly aims to find out the predisposition of LOX (G473A) and NQO1 (C609T) polymorphisms and present a comparison between the population (habitually exposed to processed arecanut and smokeless tobacco products) of a metro-city Kolkata and the tea-garden workers of Darjeeling district of West Bengal. Settings and Design: Subjects for the study was recruited from various oral health check-up camps organized in the tea-gardens of Darjeeling district and Kolkata city. Materials and Methods: Genotyping analysis was done through a Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP)-based approach. Statistical Analysis Used: A two-way contingency table analysis software (JAVASTAT: http://statpages.org/ctab2 × 2.html) using 95% confidence interval was used to study the distribution of genotypes among the populations. A P < 0.05 was considered to be significant. Results: The results indicates both the heterozygous and homozygous carriers of NQO1 C > T (609) was found to be significantly higher among the north Bengal tea-garden workers [OR 0.480 (0.280-0.82) P = 0.01; 0.218 (0.091-0.524) P = 0.0001], respectively. Interestingly CT (21% in both) and TT (8% and 7%, respectively) were found to be equally distributed in the two populations. For LOX G > A (473) a significantly higher number of Kolkata individuals were found to carry the heterozygous GA allele in individuals aged <30 years [OR 3.779 (1.684-6.547) P = 0.001]. However, none were carrier of heterozygous GA allele of Kolkata population as compared with 29% north Bengal tea-garden workers aged above 31 years. Conclusions: A close observation of occurrence of oral diseases over time among such a population will be helpful to identify risk genotypes responsible for betel quid-induced oral diseases.